Good practice report : learning and teaching across cultures. - Leask, Betty; Wallace, Jan (Australian Learning and Teaching Council, 2011)
This report: summarises the good practices and key outputs emerging from Australian Learning and Teaching Council Ltd (ALTC) projects and fellowships relating to learning and teaching across cultures; provides a review of national and international literature related to learning and teaching across cultures, particularly that which identifies practical interventions and strategies to improve student learning outcomes identifies areas in which further work or development are needed and makes a number of recommendations to address these. [Overview]